Parenting Stress in Mothers of Children with Disabilities: A Comparative Study - Shafaq Ahmad, Sarwat J. Khanam (Pakistan Journal of Psychology, 2016)
This study aimed to explore the differences in the level of parenting stress among the mothers of children with hearing impairment (C-HI), mothers of children with intellectual disabilities, mild (C-ID), and mothers of children without any disability (C-WOD). The sample comprised of 145 mothers of children divided into: mothers of C-HI, (N=56); mothers of C-ID (N= 37); and mothers of C-WOD (N=52). Parenting Stress Index (Abidin, 1995) was administered to measure the stress related to parenting. One Way ANOVA indicated that there is significant difference in the level of parenting stress between mothers of C-HI, mothers of C-ID and mothers of C-WOD. Post hoc comparisons using Tukey’s HSD indicated higher level of parenting stress in both mothers of C-HI and mothers of C-ID in contrast to mothers of C-WOD. However, the mean difference between mothers of C-HI and mothers of C-ID was found to be insignificant. These findings are suggestive of higher parenting stress in mothers of children with disabilities. Limitations and avenues for future research were suggested.